FACULTY- STUDENT MENTORSHIP PROGRAM FOR PRE-CLINICAL MEDICAL STUDENT AT CHITWAN MEDICAL COLLEGE, NEPAL: STUDENT PERSPECTIVE - Khetan, Vriddhi; Bastola, Samragyi; Dhungana, Shiwanu; Karki, Sirisa (Journal of Chitwan Medical College, 2024)
Preclinical undergraduate medical studies boast a massive shift from the traditional high school and higher-secondary school educational environment. The vast curriculum load, different new forms of teaching-learning methods, performance pressure added to the separation anxiety from family challenges the newly admitted students both physically and mentally. Guidance and support is vital to navigating the intricate pathways of academics. In order to address this issue, the newly admitted pre-clinical undergraduate medical students are supported with the Faculty-Student Mentorship Program at Chitwan Medical College. This unique initiative not only creates a support and guidance system but also helps maintain a long-lasting relationship with the faculties at the institute. We believe it is a single stop solution to address various problems of undergraduate students fighting a battle mentally, emotionally and academically.